Exploring Shamanic and Blackmagic Practices in the Movie Santet Segoro Pitu - Anggun Anis Safitri; Teguh Sulistyo; Nara Sari (Sintuwu Maroso Journal of English Teaching, 2025)
This report presents a semiotic analysis of the Indonesian horror film â€œSantet Segoro Pituâ€ using Roland Barthes' framework, which includes denotation, connotation, and myth. This study adopts a descriptive-qualitative method, with the film â€œSantet Segoro Pituâ€ as the main object. The primary research instrument is Roland Barthes' semiotic approach, which is used to uncover the meaning of signs in the film through three levels of signification: denotation, connotation, and myth. Data collection techniques include watching the entire film on Netflix, using screenshots as documentation, conducting in-depth observations of symbols, and applying triangulation methods. By examining seven key symbolsâ€”the black magic â€œSantet Segoro Pitu,â€ the mysterious package, the seven seas, the shaman, the Suanggi ghost, the Ruwatan ritual, the offerings, and the antagonist shaman's altarâ€”this study aims to uncover the deeper cultural, social, and ideological messages embedded in the film. This analysis demonstrates how the film leverages traditional Indonesian beliefs about shamans and black magic to construct a narrative that reflects societal anxieties, the enduring power of local folklore, and the tension between traditional and modern practices.